1996
DOI: 10.3354/dao024077
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of lesions in bay scallops Argopecten irradians attributed to Perkinsus karlssoni (Protozoa, Apicomplexa)

Abstract: ABSTRACT-Leslons found in bay scallops Argopecten ~r r a d imore than 1 organism associated with this name which ans imported into Atlantic Canada for culture were attributed may later be described outside the genus Perkinsus, to a parasite Perklnsus karlssonj It appears, however, that Bay scallops Argopecten irradians imported into stages froin several organisms were combined to create the life cvcle of P karlsson~. (McGladdery et al. 1991, McGladdery et al. 1993). There are significant differences, howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2000
2000
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 13 publications
0
14
0
1
Order By: Relevance
“…P. karlssoni is no longer considered to be a valid species. Thus, the identity of the pathogen that caused the disease in Argopecten irradians in Atlantic Canada and eastern USA remains unknown (Goggin et al 1996). The possibility of synonymy between P. chesapeaki and P. andrewsi (Dungan et al 2002) and between P. olseni and P. atlanticus based in the homology found in the nontranscribed regions of the rRNA cluster has also been postulated (Goggin 1994, Murrell et al 2002.…”
Section: Introductionmentioning
confidence: 99%
“…P. karlssoni is no longer considered to be a valid species. Thus, the identity of the pathogen that caused the disease in Argopecten irradians in Atlantic Canada and eastern USA remains unknown (Goggin et al 1996). The possibility of synonymy between P. chesapeaki and P. andrewsi (Dungan et al 2002) and between P. olseni and P. atlanticus based in the homology found in the nontranscribed regions of the rRNA cluster has also been postulated (Goggin 1994, Murrell et al 2002.…”
Section: Introductionmentioning
confidence: 99%
“…A subsequent study on this parasite, however, concluded that it was not a valid Perkinsus species (Goggin et al 1996).…”
Section: Historical Perspectivementioning
confidence: 99%
“…The pathogen has been associated with host lesions (Goggin et al, 1996), loss in weight (Ray, 1954), changes in physiological processes (Paynter, 1996), and even mass mortalities (Burreson & Ragone Calvo, 1996). In Galicia, several clam mortalities have occurred since 1989-90, Perkinsus being associated with them (Figueras et al, 1992).…”
Section: Introductionmentioning
confidence: 99%